(untitled) (Research, Society and Development, 2022)
Hemangioblastomas (HBs) are benign neoplasms commonly located in the cerebellum and spinal cord and may arise sporadically or related to von Hippel-Lindau Syndrome (VHL). When there is an association with VHL, multifocal tumors may arise, unlike sporadic tumors, which are isolated. VHL is a hereditary disease related to the development of benign and malignant tumors, the most common being central nervous system hemangioblastomas and retinal angiomas. The disease is caused by the inefficacy of the Tumor Suppressor Gene VHL (pVHL) in an allolo on chromosome 3p25-26. The presence of VHL in patients with HBs leads the patient to a worse prognosis, as it facilitates metastatization. Thus, the aim of the following review is to analyze the prevalence of von Hippel-Lindau syndrome in patients with central nervous system (CNS) hemangioblastomas. This is a systematic bibliographic review that used the PubMed, SciELO and Google Scholar platforms as databases for research of scientific articles, with a time frame between 2016 and 2022, in English. According to the search engine, 4 results were found after the exclusion criteria in the PubMed and Google Scholar databases. It was found, therefore, that there is a moderate prevalence of HLV in patients with CNS HBs. Among the studies, the lowest prevalence rate of HlV in patients with HBs was 23%, while the highest rate was approximately 60%, with an overall average of ± 39.2%, when considering all studies involving these patients.